Spondyloarthropathy - Is sacroiliac joint imaging sufficient? A study of 431 patients - Gupta, Saurabh; Nischal, Neha; Sharma, Lucky; Gupta, Rajiva; Singh, Jatinder Pal (Indian Journal of Radiology and Imaging, 2019)
Background: Sacroiliac (SI) joint involvement (sacroiliitis) is considered as major criteria for diagnosing Spondyloarthropathy (SpA), although involvement of spine and hip can also occur. The aim of our study was to assess the utility of including sagittal short-tau inversion recovery (STIR) sequence of dorsolumbar spine and coronal STIR/proton density (PD) fat saturated sequence through both hips, to routine SI joint magnetic resonance (MR) imaging protocol, in patients clinically suspected to have SpA. Material and Methods: A retrospective observational study was conducted between February 2013 and February 2018 on clinically suspected SpA patients referred to our department for imaging. The images obtained using this new SI joint protocol were evaluated for findings suggesting SpA diagnosis as per the Assessment of SpondyloArthritis international Society criteria. Other differentials for similar symptoms were also looked for. Results: Of the 431 patients (313 M and 118 F), 255 had features confirming the diagnosis of SpA and 176 had no radiological manifestations of SpA (56 were normal and 120 had other findings to suggest clinical symptoms; e.g., degenerative SpA, Pott’s spine, skeletal metastases, early AVN of hip, cysticercus, iliofemoral impingement). 19/255 patients had normal SI joints but other findings to suggest diagnosis of SpA, e.g. romanus lesions, costovertebritis/costotransversitis, pubic symphysitis, inflammatory hip arthropathy, enthesitis, iliofemoral/trochanteric bursitis. 33/61 patients with chronic sacroiliitis had disease activity in spine or hip. Conclusion: Inclusion of sections through dorsolumbar spine and both hips to routine SI joint protocol, helped in identifying: (a) early disease in 19 patients, who had normal SI joints and may have otherwise been missed with routine only SI joint imaging, (b) additional findings in SpA-related sacroiliitis, (c) disease activity in chronic sacroiliitis, and (d) other causes of low back pain and thus helped in further patient management.
Keywords: MRI; sacroiliitis; spondyloarthropathy